2017
DOI: 10.1177/0033354917706968
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Fall-Related Injury due to Adverse Weather Events, Philadelphia, Pennsylvania, 2006-2011

Abstract: The association between the number of fall-related ED visits and weather-related fall injuries, age, and timing suggests that many events occurred en route to work in the morning. Promoting work closures or delaying openings after severe winter weather would allow time for better snow or ice removal, and including "fall risk" in winter weather advisories might effectively warn morning commuters. Both strategies could help reduce the number of weather-related fall injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 19 publications
(38 reference statements)
1
22
1
5
Order By: Relevance
“…Slipping on ice-covered surfaces was the most frequent fall injury in the working and elderly age groups, which is in concordance with studies carried out in Norway, Finland, the UK, the USA, and Iran (Bulajic-Kopjar 2006;Flinkkilä et al 2011;Mardani-Kivi et al 2014;Gevitz et al 2017;Ralis 1981). These findings suggest that preventive measures in Shenkursk District and settings with similar climatic Other factors* 8 (9.5) 14 (4.8) 56 (7.6) 26 (5.9) *Combines categories accounting for < 5% of observations in all age groups ** p-values for group comparisons on all presented characteristics are < 0.001 conditions should primarily target removing ice and preventing slipping on icy surfaces, for example, by spreading sand and wearing shoes with high-friction outsoles or spikes.…”
Section: Discussionsupporting
confidence: 85%
“…Slipping on ice-covered surfaces was the most frequent fall injury in the working and elderly age groups, which is in concordance with studies carried out in Norway, Finland, the UK, the USA, and Iran (Bulajic-Kopjar 2006;Flinkkilä et al 2011;Mardani-Kivi et al 2014;Gevitz et al 2017;Ralis 1981). These findings suggest that preventive measures in Shenkursk District and settings with similar climatic Other factors* 8 (9.5) 14 (4.8) 56 (7.6) 26 (5.9) *Combines categories accounting for < 5% of observations in all age groups ** p-values for group comparisons on all presented characteristics are < 0.001 conditions should primarily target removing ice and preventing slipping on icy surfaces, for example, by spreading sand and wearing shoes with high-friction outsoles or spikes.…”
Section: Discussionsupporting
confidence: 85%
“…However, our data revealed no difference in in-hospital mortality post-hurricane. Numerous research studies state that falls are characterized by high medical and social costs, and that after a devastating event, those costs are likely to increase (Florence et al 2018;Gevitz et al 2017). Nonetheless, this study found no significant difference in medical costs after the hurricane.…”
Section: Discussioncontrasting
confidence: 66%
“…Some studies associated the increase in fall-related injury rates with winter harsh weather conditions 20 , 27 , 28 . In Pennsylvania, the largest demand for emergency services – mainly for falls, accounting for 8% of cases 28 , – occurred two days after snow or ice storm. In Canada, seasonal peaks of hip fractures 27 (12%) occurred mainly within four to five days after the hail and snow warnings.…”
Section: Discussionmentioning
confidence: 99%